Molecular mechanisms for anthelmintic resistance in strongyle nematode parasites of veterinary importance. Issue 2 (15th June 2016) - Whittaker, J. H.; Carlson, S. A.; Jones, D. E.; Brewer, M. T.
Abstract : Veterinarians rely on a relatively limited spectrum of anthelmintic agents to control nematode parasites in domestic animals. Unfortunately, anthelmintic resistance has been an emerging problem in veterinary medicine. In particular, resistance has emerged among the strongyles, a group of gastrointestinal nematodes that infect a variety of hosts that range from large herbivores to small companion animals. Over the last several decades, a great deal of research effort has been directed toward developing an understanding of the mechanisms conferring resistance against the three major groups of anthelmintics: macrocyclic lactones, benzimidazoles, and nicotinic agonists. Our understanding of anthelmintic resistance has been largely formed by determining the mechanism of action for each drug class and then evaluating drug‐resistant nematode isolates for mutations or differences in expression of target genes. More recently, drug efflux pumps have been recognized for their potential contribution to anthelmintic resistance. In this mini‐review, we summarize the evidence for mechanisms of resistance in strongyle nematodes.